2013
DOI: 10.3382/ps.2012-02974
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and quantification ofListeria monocytogenes in chicken offal at the retail level in Malaysia

Abstract: A total of 216 chicken offal samples (chicken liver = 72; chicken heart = 72; chicken gizzard = 72) from wet markets and hypermarkets in Selangor, Malaysia, were examined for the presence and density of Listeria monocytogenes by using a combination of the most probable number and PCR method. The prevalence of L. monocytogenes in 216 chicken offal samples examined was 26.39%, and among the positive samples, the chicken gizzard showed the highest percentage at 33.33% compared with chicken liver (25.00%) and chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…Small ruminants, especially sheep, are mostly affected (OIE 2014). L. monocytogenes has been isolated from meat and/or milk of goats, sheep, cattle, pig, chicken, quail, partridge, ostrich and buffaloes Rahimi et al 2012;Derra et al 2013;Hasegawa et al 2013;Kuan et al 2013;Ndahi et al 2014), fish and fishery products (Jayasekaran et al 1996;Karunasagar & Karunasagar 2000;, ice creams, vegetables, other ready-to-eat foods (Lambertz et al 2012;Lambertz et al 2013;Mateus et al 2013;Poulsen & Czuprynski 2013), seafood ) and mushroom production facility (Viswanath et al 2013). In the northern hemispheres, listeriosis has a distinct seasonal occurrence, probably associated with seasonal feeding of silage with the highest prevalence during December through May.…”
Section: Epidemiology Transmission and Spreadmentioning
confidence: 99%
“…Small ruminants, especially sheep, are mostly affected (OIE 2014). L. monocytogenes has been isolated from meat and/or milk of goats, sheep, cattle, pig, chicken, quail, partridge, ostrich and buffaloes Rahimi et al 2012;Derra et al 2013;Hasegawa et al 2013;Kuan et al 2013;Ndahi et al 2014), fish and fishery products (Jayasekaran et al 1996;Karunasagar & Karunasagar 2000;, ice creams, vegetables, other ready-to-eat foods (Lambertz et al 2012;Lambertz et al 2013;Mateus et al 2013;Poulsen & Czuprynski 2013), seafood ) and mushroom production facility (Viswanath et al 2013). In the northern hemispheres, listeriosis has a distinct seasonal occurrence, probably associated with seasonal feeding of silage with the highest prevalence during December through May.…”
Section: Epidemiology Transmission and Spreadmentioning
confidence: 99%
“…As a result, the combination of these two methods (MPN and PCR) has proved to be simpler, more reliable, and less laborious. In addition, MPN is generally preferred when the level of L. monocytogenes in the sample is expected to be low, i.e., ≤ 10-100 MPN/g [10]. This was further proved by a study conducted by Chen et al [4] as the MPN method was observed to be more precise than direct plating for most of the samples where the levels of L. monocytogenes were low.…”
Section: Discussionmentioning
confidence: 53%
“…have reported that L. monocytogenes has been isolated from various types of food such as fish, chicken, beef, and poultry [3,10]. When it comes to cat and dog food, there are a very limited data with regard to the contamination of these pet food diets by L. monocytogenes around the world.…”
Section: Minimum Median Maximummentioning
confidence: 99%
“…This fact represents a main advantage over previously published procedures which take a minimum of 40 h only in the incubation step, [23,44,45] and may take even longer if the confirmation steps are performed by traditional microbiology or conventional PCR [22,[46][47][48]. Additionally, our method demonstrated suitability for application with two different detection chemistries, SYBR Green intercalating dye, which is a more economic approach, and with a hydrolysis probe, which offers additional specificity.…”
Section: Discussionmentioning
confidence: 77%
“…In these methods, positive tubes are generally confirmed by traditional microbiology, but in recent years the combination with molecular techniques, such as PCR/qPCR, has enhanced the applicability of these protocols. According to previous studies, MPN is especially useful for low-level bacterial contamination (<10-100 MPN/g) [22][23][24].…”
Section: Introductionmentioning
confidence: 97%